Direito em rede e a jurisdição democratizada: a necessidade de se alcançar respostas corretas para litígios envolvendo direitos transindividuais - Gadenz, Danielli (2014)
Given the dynamism of the current world - network society – it's emerging disputes involving transindividual rights, which are not getting the proper judicial assistance from a state that says (or intend to be) Democratic of Law. The issue introduces itself from the attachment to the rationalist paradigm, on one hand, and the search for implementing rights, without regarding the Constitution, becoming the judge the protagonist of the process, on the other hand. The fact is that the current jurisdiction does not comply with what is expected of it in a Democratic State. So, it is necessary a paradigm and judicial culture change in order to achieve a democratized model of jurisdiction. This is defended from the perspective of network law, a model built from notions of coherence and integrity of the court decisions and sustained by the proper reasoning (not motivation) of decisions in the constitutional principles, aiming to achieve correct answers to disputes involving transindividual rights. Only so will be possible to speak of democratized jurisdiction, aligned to the paradigm of Democratic State of Law and capable of providing a fair judicial protection to their citizens.